The Management of Learning and Training at the National Police in Improving the Professionalism of the National Police - Muh Elia Wasono Mastoro; Dedi Mulyasana; Sofyan Sauri; Deti Rostini (Journal of Islamicate Studies, 2020)
The Management of Learning and Training at the National Police in Improving the Professionalism of the National Police is developed to build the effectiveness of the process in education and training in facing the development and growth of current and future social culture. Aimed at finding a picture related to the objectives and focus. Related questions: 1) How to find out the aims and training programs of the POLRI in improving the professional non-commissioned officer of the National Police; 2) How to assess the implementation of POLRI's objectives and education and training programs in improving POLRI non-commissioned personnel? ; 3) How to find out the problems faced by POLRI leaders in implementing POLRI objectives and education and training programs in improving the professional non-commissioned officers of POLRI ?; 4) How to find out the solutions and efforts to improve in the future the pattern of training for professional improvement of the POLRI NCO ?; 5) How are the efforts of the POLRI educational institution in making the learning process effective in increasing the quality of student graduation? The results showed that performance must include the synergy element of ability (Ability), motivation (Motivation), and opportunities (Opportunity) that can be captured. Whereas competence must include knowledge, teaching skills with various relevant methods, as well as attitudes and behaviors that are able to show figures as appropriate examples for students.